Inovasi Pelayanan Publik dalam Pengadaan Transportasi Umum: Studi Trans Metro Deli (Lembaga Pengembangan Kinerja Dosen, 2025)
In supporting public services, the government provides the best for the community, so innovation or renewal is needed. There is innovation in the transportation sector so that the needs of the community are increasingly met. This study aims to analyze public service innovations provided by the government in the procurement of public transportation, namely Trans Metro Deli Medan. The theory used is Public Service Innovation by Everett M. Rogers. The method used is the Systematic Literature Review (SLR) which focuses on literature studies. The results of the study on public service innovation indicators show that the Trans Metro Deli public service innovation has relative advantages in terms of fleet and good service quality, Trans Metro Deli is also in accordance with what is expected by the government and the community to be able to reach community mobility. In its implementation, the community experienced difficulties in using non-cash cards at the beginning, although no tariff fees were charged. BRT has also been proven to be acceptable to the community as shown by the increase in BRT users, as well as the ease of observing that the emergence of this public service innovation has worked and produced a better service to the community.